The timing of executive function development is associated with growth in math achievement from preschool through second grade. (February 2023) - Ahmed, Sammy F.; Montroy, Janelle; Skibbe, Lori; Bowles, Ryan; Morrison, Frederick
Abstract: We examined whether the timing of executive function (EF) development was associated with growth in children's math achievement across eight measurement occasions from preschool through second grade. Using a prospective longitudinal sample of 351 children, we found that children who developed EF later, entered preschool with the lowest levels of math performance and did not catch-up to their intermediate or early EF developing counterparts despite exhibiting a similar math growth rate through second grade. This trend was also observed after controlling for children's biological sex, early language skills, and socioeconomic background. These findings suggest that developing EF late might place children at a unique risk for math difficulties independent of important child and family level characteristics and can provide insights for instructional strategies that take into account differences in children's EF development. Highlights: Developing executive function early was associated with higher math trajectories. Developing executive function late may be a unique risk factor for math difficulties. Instructional practices should account for timing of executive function development.